Serological Studies of West Nile Virus in a Liver Transplant Population - LE Nicolle; A Gutkin; G Smart; M Dawood; M Drebot; P Van Caeseele; A Giulivi; GY Minuk (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Solid organ transplant populations are at increased risk for serious clinical manifestations of West Nile virus (WNV) infection.